Neuromuscular strain as a contributor to cognitive and other symptoms in chronic fatigue syndrome: hypothesis and conceptual model - Rowe, Peter C.; Fontaine, Kevin R.; Violand, Richard L. (Frontiers in Physiology, 2013)
Individuals with chronic fatigue syndrome (CFS) have heightened sensitivity and increased symptoms following various physiologic challenges, such as orthostatic stress, physical exercise, and cognitive challenges. Similar heightened sensitivity to the same stressors in fibromyalgia (FM) has led investigators to propose that these findings reflect a state of central sensitivity. A large body of evidence supports the concept of central sensitivity in FM. A more modest literature provides partial support for this model in CFS, particularly with regard to pain. Nonetheless, fatigue and cognitive dysfunction have not been explained by the central sensitivity data thus far. Peripheral factors have attracted attention recently as contributors to central sensitivity. Work by Brieg, Sunderland, and others has emphasized the ability of the nervous system to undergo accommodative changes in length in response to the range of limb and trunk movements carried out during daily activity. If that ability to elongate is impaired—due to movement restrictions in tissues adjacent to nerves, or due to swelling or adhesions within the nerve itself—the result is an increase in mechanical tension within the nerve. This adverse neural tension, also termed neurodynamic dysfunction, is thought to contribute to pain and other symptoms through a variety of mechanisms. These include mechanical sensitization and altered nociceptive signaling, altered proprioception, adverse patterns of muscle recruitment and force of muscle contraction, reduced intra-neural blood flow, and release of inflammatory neuropeptides. Because it is not possible to differentiate completely between adverse neural tension and strain in muscles, fascia, and other soft tissues, we use the more general term “neuromuscular strain.” In our clinical work, we have found that neuromuscular restrictions are common in CFS, and that many symptoms of CFS can be reproduced by selectively adding neuromuscular strain during the examin